Survey on the impact of VAT on libraries and the scientific publication markets - Editor, Journal (LIBER Quarterly: The Journal of the Association of European Research Libraries, 2006)
Within the European Union (EU), printed and electronic versions of publications are treated differently. Whereas books, newspapers and periodicals are subject to a reduced rate of VAT, electronic publications, of all types, are charged with the full rate of VAT. These regulations have several consequences for European libraries and the market for scholarly publications in Europe, not least in regard to the change from printed to electronic publications.